Students classroom activeness as correlate of academic achievement in english language in Ibadan metropolis (2016)
The study investigated students' classroom activeness as correlate of their academic achievement in English Language in Ibadan Metropolis, Oyo State. Three research questions were developed to guide the study. An ex postfacto research design of survey research type and the target population consists is SSSII Students in Ibadan Metropolis. Using simple random sampling technique, 150 SSS II students across secondary schools in Ibadan metropolis were selected as respondents for the study. Students' classroom active participation rating scale was used for data collection. Descriptive statistics and pearson product moment correlation were used in the data analysis. The findings of the study revealed that: majority of the students with the mean of 2.50 and above do participate actively during English Language lesson. Also, there is low negative correlation (r = -.103, p=.208) between students’ questioning/answering questions in the classroom and academic achievement in English Language. Also, there is low negative correlation (r = 114, p=.164) between students' initiation/contribution to classroom discussion and academic achievement in English Language. It was therefore, recommended that teachers of English Language should motivate students to participate more actively in the classroom by asking or answering questions during English Language lessons.